Availability, type, brand, and price as preference of shade matching tools for dentists in Jakarta’s dental sector: a cross-sectional study - Octarina, Octarina; Tirtania, Carinna; Maringka, Stella Maria Fidela; Rinanti, Astri; Razak, Fathilah Abdul (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Shade selection in aesthetic dental procedures remains a challenge in dentistry. This challenge arises due to the high complexity of natural tooth color. The use of a shade guide as a form of communication between dentists and dental technicians is highly subjective, leading to the emergence of digital methods that offer a higher level of accuracy and consistency. The purpose of this research is to assess the type, brand, and price as preference of shade matching tools for dentists in Jakarta’s dental sector. Methods: The survey was conducted as a descriptive observational study using cluster sampling through questionnaires and a review of shade matching product catalogs from 30 dental suppliers, 4 dental clinics, and 7 dental laboratories in Jakarta. Results: There is a variety in the price and availability of shade matching products sold by dental suppliers in Jakarta, with VITA branded products dominating the market, including VITAPAN Classical (25%), VITA Classical (15%), VITA 3D Master (12%), and Ivoclar Vivadent (12%). In both clinics and dental laboratories, all respondents reported using visual methods, with VITA Classical and VITA 3D Master being the most commonly used products. Conclusion: Shade matching products available from dental suppliers, as well as their use in clinics and laboratories in Jakarta, are predominantly based on visual methods, with VITA Classical and VITA 3D Master being the most preferred shade guides. Digital shade matching methods are rarely encountered, mainly due to product complexity, cost, distribution limitations, and lack of training.Ketersediaan, tipe, merk, dan harga sebagai preferensi alat pencocokan warna oleh dokter gigi di sektor kedokteran gigi jakarta: survei potong lintangPendahuluan: Pemilihan warna dalam prosedur estetika menjadi tantangan dalam kedokteran gigi. Tantangan ini muncul karena warna alami gigi memiliki kompleksitas yang tinggi. Penggunaan shade guide sebagai bentuk komunikasi antara dokter gigi maupun teknisi laboratorium bersifat sangat subjektif sehingga muncul metode digital yang menawarkan tingkat akurasi dan konsistensi yang lebih tinggi. Tujuan penelitian ini adalah untuk mengevaluasi jenis, merek, dan harga sebagai preferensi alat pemilihan warna bagi dokter gigi di Jakarta. Metode: Survei dilakukan sebagai penelitian observasional deskriptif menggunakan sampling klaster dengan mengajukan pertanyaan serta penelahaan katalog produk shade matching pada 30 dental supplier, 4 klinik gigi, dan 7 laboratorium gigi yang ada di Jakarta. Hasil: Terdapat berbagai variasi dalam harga dan ketersediaan produk shade matching yang di jual dental supplier di Jakarta, dengan dominasi produk bermerek VITA, yaitu VITAPAN Classic (25%), VITA classical (15%), VITA 3D Master (12%) dan Ivoclar Vivadent (12%). Pada klinik dan laboratorium gigi didapatkan hasil bahwa seluruhnya menggunakan metode visual dengan produk yang paling banyak digunakan yaitu VITA Classical (27%) dan 3D Master (36%). Simpulan: Produk shade matching yang tersedia di dental supplier serta penggunaannya di klinik dan laboratorium Jakarta didominasi metode visual dengan VITA Classical dan 3D Master menjadi shade guide yang paling digemari. Metode pencocokan warna dengan metode digital jarang ditemui disebabkan kompleksitas produk, kendala harga, distribusi, dan kurangnya pelatihan.